Predictors of Hospital Length of Stay among Patients with Low-risk Pulmonary Embolism - Li Wang; Onur Baser; Phil Wells; W. Frank Peacock; Craig I. Coleman; Gregory J. Fermann; Jeff Schein; Concetta Crivera (Journal of Health Economics and Outcomes Research)
**Background:** Increased hospital length of stay is an important cost driver in hospitalized low-risk pulmonary embolism (LRPE) patients, who benefit from abbreviated hospital stays. We sought to measure length-of-stay associated predictors among Veterans Health Administration LRPE patients.